Formation Constants of La(III), Ce(III), Pr(III), Nd(III), Sm(III) and Y(III) Ternary Chelates - Kolhe, Vishnu; Dwivedi, K. (Asian Journal of Chemistry, 2010)
Equilibrium studies in metal-disodium salt of ethylene glycol bis (2-amino ethyl ether)-N,N,N´,N´-tetraacetic acid (ligand A)—L proved the formation of ternary complexes of the type MAL. The ligands (L) used are anthranilic acid, 3-methylanthranilic acid and monosodium salt of 5-sulfoanthranilic acid. Equilibrium constants corresponding to various equilibria have been measured at 25ºC and at three different ionic strengths of 0.05 M, 0.10 M and 0.15 M (NaNO3). The metal ions taken for the present studies are La(III), Ce(III), Pr(III), Nd(III), Sm(III) and Y(III).